Peripheral benzodiazepine receptors are colocalized with activated microglia following transient global forebrain ischemia in the rat - Stephenson, DT (J Neurosci, 1995)
In mammalian brain the expression of peripheral benzodiazepine receptors (PBRs) can be markedly induced following different types of neuronal injury. PBRs are believed to be expressed on non-neuronal cells in the brain, yet the specific cell type that expresses these receptors following CNS insult has not been defined. In the present study, we investigated the effects of transient global forebrain ischemia on PBRs by autoradiographic localization of 3H-PK11195 binding. The distribution of PBRs was compared to glial fibrillary acidic protein (GFAP) as a marker for astrocytes and OX42 as a marker for microglia. Five to 6 d following four-vessel occlusion (4-VO), an increase in PBRs was seen in the CA1 region of all 15 brains examined. In brains from rats subjected to 4-VO, microglia were selectively activated in stratum pyramidale of the CA1 layer. In contrast, astrocytes appeared to be activated in multiple hippocampal cell layers including stratum radiatum and stratum oriens. Activated astrocytes were also found in regions that did not exhibit increased 3H-PK11195 binding. In some brains, selected regions of secondary lesion, specifically necrotic thalamic nuclei and the isocortex were found to be strongly immunoreactive for OX42 but lacked GFAP immunoreactive cells. In adjacent sections, these same regions displayed high densities of 3H-PK1195 binding. These observations lend further support to the application of 3H-PK11195 binding as a marker of neuronal injury in the brain. Furthermore, the data strongly suggest that activated microglia rather than astrocytes express PBRs following ischemic insults.